Analisis Kepuasan Pengguna Transportasi Umum Ojek Online (Gojek) Melalui Instrumen Layanan - Mohammad Farhan Appliansyach; Qian Nugraha Sugiyo; Dimas Bayu Maulana; Siti Sahara (FEB Universitas Maritim Semarang, 2023)
In Indonesia, online motorcycle taxis are the largest public transportation with a very large number of partners and fleets, covering all parts of Indonesia. As a profit-oriented mode of public transportation, paying attention to customer satisfaction is a necessity. One of the efforts that can be done is to provide quality services. In fact, this study aims to find out how online transportation users respond by looking at the service elements provided by service providers. Scientific studies are used as a logical way to prove reliable research results, and in this study using quantitative methods and statistical analysis of linear regression. The subjects of this study were users of the online ojek public transportation mode in the student MPLM UNJ 2022,Jakarta. The results of the study provide an overview, in general, respondents are satisfied with the presence of nline motorcycle taxis. This is very helpful and facilitates user activities. However, there are still things that need to be improved, such as comfort and safety standards. Statistically, service has a significant effect on online motorcycle taxi user satisfaction.